2014
DOI: 10.20452/pamw.2071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome, echocardiographic assessment, neurohormonal and collagen turnover markers in low-fl ow severe aortic stenosis with high transvalvular gradient

Abstract: INTRODUCTION Patients with severe aortic stenosis (AS), high mean gradient (HMG), and preserved left ventricular ejection fraction (LVEF) may present with paradoxical "low flow" (LF). OBJECTIVES The aim of the study was to assess the potential effect of cardiac collagen metabolism on the HMG/LF phenomenon in patients with severe AS and to determine a clinical and echocardiographic pattern of these patients. PATIENTS AND METHODS We assessed a clinical status of 89 patients, aged over 64 years, with severe AS, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…17 In evaluating the severity of valvular heart disease, a sensitive biomarker would be very useful, potentially providing support to clinical management in asymptomatic patients with AS. 8,12,18 A previous study found that AS is strongly associated with increased NT-proBNP levels.…”
Section: Resultsmentioning
confidence: 99%
“…17 In evaluating the severity of valvular heart disease, a sensitive biomarker would be very useful, potentially providing support to clinical management in asymptomatic patients with AS. 8,12,18 A previous study found that AS is strongly associated with increased NT-proBNP levels.…”
Section: Resultsmentioning
confidence: 99%
“…Although CITP and PIIINP were found to be strongly associated with HF, especially HFrEF and cardiac dysfunction, circulating collagen metabolites were not accurate surrogate biomarkers for myocardial fibrosis in patients with AS [114]. However, the concentration of circulating PIIINP correlated positively with PAWP and inversely with LV ejection fraction and stroke volume index [115]. At the same time, downregulated expression of microRNA-19b, which elucidates collagen fibril cross-linking, predicted altered myocardial collagen network in AS patients, especially in those who had HF [116].…”
Section: Biomarkersmentioning
confidence: 99%
“…Using the optimum NT-proBNP cut-off point of 515 pg/ml, they reported event-free survival rates at 1 and 2 years of 93% and 57%, respectively, in patients with NT-proBNP levels of less than 515 pg/ ml, compared with 50% and 31%, respectively, in those with NT-proBNP levels exceeding 515 pg/ml. 32 The authors concluded that the measurement of NT-proBNP provides valuable prognostic information in patients with asymptomatic moderate-to-severe AS.In a subset of patients with severe AS, high gradient, and preserved systolic function, Piestrzeniewicz et al 33 found low transvalvular flow to be related to high blood levels of NT-proBNP. In addition, they found an inverse relation between procollagen III N-terminal propeptide and stroke volume index, indicating enhanced tissue fibrosis as an underlying pathology.…”
mentioning
confidence: 99%
“…In a subset of patients with severe AS, high gradient, and preserved systolic function, Piestrzeniewicz et al 33 found low transvalvular flow to be related to high blood levels of NT-proBNP. In addition, they found an inverse relation between procollagen III N-terminal propeptide and stroke volume index, indicating enhanced tissue fibrosis as an underlying pathology.…”
mentioning
confidence: 99%